Hermafroditism in Orestias agassi (carachi gris) from Titicaca lake in Puno, Peru: Case Report - Amaru Chambilla, Glicerio R. (2016)
The hermaphroditism in the nature of the ﬁsh, result in some species a strategy of reproductive behaviour but in general, its frequency of apparition result a event biological of character rare, for not always such conduct is associated to the same conditions environmental. The objective of the present research was to describe hermaphroditism in Orestias agassi of Titicaca lake in Puno-Peru as a case report. Since 2009, Laboratory Continental of Puno records as activities the monitoring of ﬁshery, where is evaluated inside of its main indicators the total length, standard length, total weight and bowel weight (gonads, stomach and liver). In May of 2014, corresponding to the zone of Villa Santiago-District of Pomata, Province of Chucuito, in laboratory conditions was made a probabilistic random sampling (92 individuals), to which there was an interval rank of 8,6 to 15,2cm of total length. It is identiﬁed through the observation of structured biometric analysis, an exemple with presence of both reproductive gonads, which are of 12,3cm in total length and total weight of 29,94g. It has not been observed signiﬁcant statistical differences with relation to the remainder of individuals identiﬁed in the same class of size interval (octave). It is concluded that of 3,302 individuals of the species orestias agassi analyzed in eight years, it is the ﬁrst case that is reported with hermaphroditism.